2010
DOI: 10.1016/j.nbd.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired dopaminergic neurotransmission and microtubule-associated protein tau alterations in human LRRK2 transgenic mice

Abstract: Mutations in the Leucine Rich Repeat Kinase 2 (LRRK2) gene, first described in 2004 have now emerged as the most important genetic finding in both autosomal dominant and sporadic Parkinson's Disease (PD). While a formidable research effort has ensued since the initial gene discovery, little is known of either the normal or the pathological role of LRRK2. We have created lines of mice that express human mutant wild-type (hWT) or G2019S Lrrk2 via bacterial artificial chromosome (BAC) transgenesis. In vivo analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
286
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(309 citation statements)
references
References 61 publications
22
286
1
Order By: Relevance
“…In addition, animals transgenic for LRRK2 containing the most frequent G2019S mutation show increased anxiety-related behavior (Melrose et al 2010). Moreover, LRRK2 is highly expressed in the hippocampus, in particular, in PSA-NCAM expression neuroblasts (Melrose et al 2007).…”
Section: Adult Neurogenesis In Transgenic Animal Models Of Pdmentioning
confidence: 99%
“…In addition, animals transgenic for LRRK2 containing the most frequent G2019S mutation show increased anxiety-related behavior (Melrose et al 2010). Moreover, LRRK2 is highly expressed in the hippocampus, in particular, in PSA-NCAM expression neuroblasts (Melrose et al 2007).…”
Section: Adult Neurogenesis In Transgenic Animal Models Of Pdmentioning
confidence: 99%
“…Two transgenic mouse models overexpressing human G2019S LRRK2 exhibit modest age-dependent DA neuron loss associated with accumulation of autophagosomes and mitochondrial alterations [124,125], but other G2019S LRRK2 transgenic mouse models had diminished dopamine transmission and motor deficits without detectable neuron loss [53,54]. The only I2020T LRRK2 transgenic mouse model reported to date exhibits no obvious loss of DA neurons [126].…”
Section: Direct Toxic Effects Of Lrrk2 Expression In Neuronsmentioning
confidence: 99%
“…In neurons, G2019S LRRK2 induces shortening of neurite length and, perhaps, alteration of their branching [53,56,57]. I2020T also induces the shortening and debranching of neurites [56,126].…”
Section: Effects Of Lrrk2 On Cellular Phenotypes and Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…While no overt pathological lesions were reported, the authors did reveal that phospho-tau was decreased in the WT transgenic mice. Our group (Melrose et al, 2010) also reported WT and mutant G2019S BAC mice, utilizing a human LRRK2 BAC rather than a murine BAC. Using in vivo microdialysis we demonstrated that basal extracellular dopamine levels were reduced by ~33% in G2019S BAC mice at ~8 months and an enhanced response to amphetamine challenge was noted.…”
Section: Over-expression Of Lrrk2mentioning
confidence: 99%